2011
DOI: 10.1016/j.ultsonch.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic irradiation on crystallization kinetics of potassium dihydrogen phosphate

Abstract: The ultrasound effect applied on potassium dihydrogen phosphate was investigated in a continuous crystallization system. The studied process variables were ultrasonic power (W) and residence time. The crystal size distributions of the final products obtained with and without ultrasonic power were determined and the data were evaluated by using modified form of Abegg, Stevens and Larson (ASL) model. The supersaturation limit decreased with ultrasonic waves and the crystal morphology was modified. The average cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…Use of high intensity probes causes intense cavitation and free radical generation. Further, Sayan et al [70] reported abrasive effects at higher input powers. Despite the favourable effects of ultrasonication on crystal structure, the aforementioned effects may lead to off-flavour in fats and lipids.…”
Section: Mechanism Of Sonocrystallisationmentioning
confidence: 97%
See 2 more Smart Citations
“…Use of high intensity probes causes intense cavitation and free radical generation. Further, Sayan et al [70] reported abrasive effects at higher input powers. Despite the favourable effects of ultrasonication on crystal structure, the aforementioned effects may lead to off-flavour in fats and lipids.…”
Section: Mechanism Of Sonocrystallisationmentioning
confidence: 97%
“…In general, it is observed that the supersaturation limit decreases with ultrasonic waves and crystal morphology is modified. Also, the average crystal size decreases in the presence of ultrasonic power [70]. Studies by Li et al [36] suggest that ultrasound produces a thin film surface layer on the crystal in which the crystallising molecules can better align themselves for incorporation in the unit cell.…”
Section: Mechanism Of Sonocrystallisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound has been widely reported to influence the primary nucleation process accelerating nucleation kinetics, this is typically expressed in terms of reducing the induction time and MSZW [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Ultrasound can also increase the rate of secondary nucleation, this is manifested as a reduction on the product crystal size distribution [20,22,24,31,32,[34][35][36][37][38][39][40][41][42][43]. Ultrasound can also influence crystal growth [20,25,26,36,40,[44][45][46] although the effect on crystal growth is not as dramatic as on nucleation and arises largely from enhanced mass transfer [46] and can influence crystal morphology.…”
Section: Introductionmentioning
confidence: 99%
“…These include the formation of local hot spots which arise from the large energy release on the collapse of cavitation bubbles creating highly localised regions of extremely high temperature and pressure [50,51], or due to rapid cooling which follows; shockwaves released from cavitation bubbles [52,53], promoting mass transfer and collisions between crystals and adjacent surfaces [54]. These effects of ultrasound on crystallisation have been demonstrated on pharmaceuticals and commodity chemicals including; lactose [35,39,42,55], alpha-dextrose monohydrate [20], glycine [48], p-aminobenzoic acid [47], adipic acid [28], benzoic acid [31], acetylsalicylic acid [27], protein [19] various food products [30,56,57] and in the crystallisation of inorganic materials such as potassium sulphate [26], potassium dihydrogen phosphate [32] and calcite [34]. Ultrasound has also been utilized in continuous crystallisation [28,[58][59][60].…”
Section: Introductionmentioning
confidence: 99%